Can a specific neck strengthening program decrease cervical spine injuries in a men`s professional Rugby Union team? A retrospective analysis - Naish, R.; Burnett, A.; Burrows, S.; Andrews, W.; Appleby, B. (Journal of Sports Science & Medicine, 2013)
Cervical spine injuries in Rugby Union are a concerning issue at all levels of the game. The primary aim of this retrospective analysis conducted in a professional Rugby Union squad was to determine whether a 26-week isometric neck strengthening intervention program (13-week strengthening phase and 13-week maintenance phase) was effective in reducing the number and severity of cervical spine injuries. The secondary aim was to determine whether at week five, where the program had been the similar for all players, there was increased isometric neck strength. All 27 players who were common to both the 2007-2008 and 2008-2009 seasons were included in this analysis and data was extracted from a Sports Medicine/Sports Science database which included the squad's injury records. Primary outcome variables included; the number of cervical spine injuries and the severity of these injuries as determined by the total number of days lost from training and competition. Secondary outcome variables included isometric neck strength in flexion, extension and left and right lateral flexion. Using non-parametric statistical methods, no significant differences were evident for the total number of cervical spine injuries (n = 8 in 2007-2008, n = 6 in 2008-2009) or time loss due to these injuries (100 days in 2007-2008, 40 days in 2008-2009). However, a significant (p = 0.03) reduction in the number of match injuries was evident from 2007-2008 (n = 11) to 2008-09 (n = 2). Non-significant increases in isometric neck strength were found in all directions examined. A significant reduction in the number of match injuries was evident in this study. However, no other significant changes to primary outcome variables were achieved. Further, no significant increases in isometric neck strength were found in this well-trained group of professional athletes.